A protocol to encourage accelerometer wear in children and young people. Issue 4 (7th August 2016) - McCann, Deborah Ann; Knowles, Zoe R.; Fairclough, Stuart J.; Graves, Lee E. F.
Abstract: Background: Improving compliance to physical activity (PA) monitoring is critical for obtaining valid, comparable data free from inconsistencies that occur during data reduction. The first aim of this study was to investigate children (8–11 years) and young people's (12–15 years) views on strategies to promote habitual wear of hip (ActiGraph) and wrist-worn (GENEActiv) accelerometers. The second aim was to subsequently develop a protocol to reduce participant and researcher burden and maximise accelerometer wear time data. Methods: An interpretivist methodology was used with semi-structured, mixed-gender focus groups in seven elementary ( n  = 10; 47 children) and five high schools ( n  = 10; 49 young people). Focus groups were transcribed verbatim and outcomes from deductive and inductive analysis were represented via pen profiles. Results: Deductive content analysis revealed four general dimensions: (1) participant driven compliance strategies; (2) reasons for non-compliance to wear time; (3) strategies to improve accelerometer care; (4) reasons for non-compliance to study conditions. Children perceived popular wear time compliance strategies to be: (1) sticky note reminders; (2) mobile phone reminders; (3) social conformity, whereas young people's perceptions were: (1) social conformity; (2) mobile phone reminders; (3) monetary compensation. Conclusions: Where possible, compliance strategies should accommodate the varying preferences of children and young people (CYP). It is recommended that future accelerometry based research adopts a formative phase. In the absence of a formative research phase, future research should consider the use of this informed protocol to improve compliance to PA monitoring in CYP.